The Role of Interest as a Mediator in The Relationship of Knowledge And Islamic Financial Inclusion to The Loyalty Costumers of Non-Muslim - Meilany, Ruswinalda; Fasiha, Fasiha; Moalla, Maya (Universitas Islam Negeri Raden Intan Lampung, 2025)
Islamic banking in Indonesia is experiencing rapid growth with an increase in assets by 15% in 2023, including the growth of non-Muslim customers. However, its market share is still low at 7.3%, which triggers the need to understand the customer loyalty factor, especially non-Muslims. This study aims to explore the role of interest as a mediator between Islamic financial knowledge and inclusion on the loyalty of non-Muslim customers. This study uses a quantitative method with data collection through questionnaires that are analyzed using Partial Least Square (PLS). This study focuses on the entire population of non-Muslim customers at Bank BTN Syariah Kendari Branch with sampling techniques using accidental sampling. The results of this study show that knowledge and inclusion of Islamic finance have a significant effect on customer loyalty through interest with p values of 0.022 and 0.001 smaller than 0.05 and t-statistic of 2.289 and 3.407. The study concludes that knowledge and increased Islamic financial inclusion can strengthen the loyalty of non-Muslim customers